Aesthetic Individualization in Direct Restorations Using Composite Stains. Part 1 - Golinka О. П. (Actual Dentistry, 2026)
Relevance. Generalization of modern approaches to the aesthetic individualization of direct restorations using composite dyes, as well as an analysis of the domestic market for these materials, particularly the capabilities and properties of the products of the Ukrainian manufacturer Jen Dental Ukraine. Objective: to evaluate the clinical effectiveness of dyes and colored liquid composites, determine their role in improving the optical quality of restorations, and substantiate their feasibility in dental practice. Materials and methods. The materials in the study were composite dyes and colored liquid composites from the domestic manufacturer Jen Dental Ukraine, which are used for individualization and optical modification of direct restorations. The work provides an analytical review of contemporary clinical and experimental sources on the properties and applications of these materials in dental practice. The properties of dyes in different groups (opaque, colored composites, color modifiers), their interactions with composite materials, and their effects on the optical characteristics of restorations were analyzed. Results. Clinical photo observations, within the scope of the work, confirmed the effectiveness of composite dyes in reproducing the tooth’s natural optical effects. The use of dyes enabled precise reproduction of intensities, characterization, and relief, and ensured high-quality masking of discolorations and artificial elements. In the presented clinical cases, the dyes demonstrated color stability and the ability to improve the aesthetics of restorations without increasing the volume of composite or the complexity of the technique. Conclusion. Composite dyes significantly expand the possibilities of direct restoration, allowing accurate reproduction of individual anatomical and optical characteristics of teeth, masking discolorations and artificial elements, and achieving a natural, aesthetically perfect result even when using a monochrome technique. The presence of Jen Dental Ukraine products in the domestic market expands the options available to Ukrainian dentists, providing access to high-quality composite dyes and color modifiers tailored to the needs of modern restorative dentistry. Further research should focus on the clinical assessment of the effectiveness of composite dyes in direct restorations, with analysis of specific clinical cases, to provide more practical recommendations for dentists.